2010
DOI: 10.1111/j.1750-3841.2010.01565.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression, and Genus‐Specificity Analysis of 28‐kDa OmpK from Vibrio alginolyticus

Abstract: Some Vibrio species are universal marine pathogens and Vibrio infections are often encountered due to consumption of raw or uncooked seafood. The outer membrane proteins, playing a key role in interaction between bacteria and hosts, are potential candidates for development of vaccine and markers of the genus Vibrio. In this study, the ompK (outer membrane protein K) genes of Vibrio alginolyticus, V. vulnificus, V. parahaemolyticus, V. fluvialis, and V. mimicu were cloned with 798 to 822 nucleotides encoding 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Among the virulence genes, all isolates acquire ompK followed by toxR and collagenase genes as confirmed by PCR and subsequence analysis. Furthermore, this result showed that ompK gene could be used as gene marker for Vibrio alginolyticus compared to collagenase [7,12]. Besides, in previous study by Zulkifli et al [24] toxR function as regulator for expression of the virulence factor genes in other species of Vibrio such as V. parahaemolyticus.…”
Section: Resultsmentioning
confidence: 79%
“…Among the virulence genes, all isolates acquire ompK followed by toxR and collagenase genes as confirmed by PCR and subsequence analysis. Furthermore, this result showed that ompK gene could be used as gene marker for Vibrio alginolyticus compared to collagenase [7,12]. Besides, in previous study by Zulkifli et al [24] toxR function as regulator for expression of the virulence factor genes in other species of Vibrio such as V. parahaemolyticus.…”
Section: Resultsmentioning
confidence: 79%
“…2010a); guinea pig serum against V. alginolyticus OmpK was cross‐reactive with all five Vibrio species (Li et al . 2010c) but the murine mAbs prepared in their following study were also specific to V. alginolyticus (one mAb also reacted with V. parahaemolyticus ). OmpK was further investigated as a candidate for a fish subunit vaccine; however, the relative percent survival (RPS) of homogenous strains in different studies was highly variable.…”
Section: Resultsmentioning
confidence: 89%
“…Moreover, OmpK antibodies for diagnostic purposes have also been reported with discrepant specificity in different reports (Li et al . 2010a,2010c). In these studies, recombinant OmpK has been expressed as inclusion bodies, while the immunogenicity of soluble OmpK remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The outer membrane proteins of the fish pathogen, V. parahaemolyticus , which play important roles in the interaction between bacteria and hosts, are potential candidates for the development of vaccines. It was reported that the outer membrane protein, ompK could elicit immune protection in fish species against V. parahaemolyticus infections (Ningqiu et al ., ; Li et al ., 2010; 2013). However, the inconvenience of vaccination application hindered its successful development as an effective vaccine against the deadly infection by V. parahaemolyticus in fish (Collado et al ., ; Romoren et al ., ; Clark and Cassidy‐Hanley, ; Companjen et al ., ; Plant and Lapatra, ; Fredriksen and Grip, ; Ruyra et al ., ; Vimal et al ., ).…”
Section: Discussionmentioning
confidence: 99%